2006
DOI: 10.1002/j.2161-007x.2006.tb00049.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Consideration of Counselor Education Teaching Strategies

Abstract: Counselor educators rely on a variety of teaching strategies to augment clinical instruction and enhance student learning. Such strategies include action methods, audio/video material, and self‐exploration. While using these strategies, educators are responsible for remaining sensitive to fundamental ethical issues, varied student needs, and academic/professional standards. Despite appearing straightforward and routine, this aspect of counselor education requires ongoing appraisal to ensure adherence to ethica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Many of the same concerns inherent in including artmaking in counseling and counselor education are shared with the practice of supervision. For example, Ziff and Beamish (2004) described the necessity of training in the use of the arts before implementing techniques into professional practice, Hammond and Gantt (1998) delineated ethical issues surrounding treatment of the artwork, and Morrissette and Gadbois (2006) described the potential for discomfort when participating in experiential techniques. Ethical concerns related to using art-based supervision strategies tend to coalesce around the topics of practicing outside of the scope of professional training, handling of artwork, and ensuring supervisee well-being.…”
Section: Ethical Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the same concerns inherent in including artmaking in counseling and counselor education are shared with the practice of supervision. For example, Ziff and Beamish (2004) described the necessity of training in the use of the arts before implementing techniques into professional practice, Hammond and Gantt (1998) delineated ethical issues surrounding treatment of the artwork, and Morrissette and Gadbois (2006) described the potential for discomfort when participating in experiential techniques. Ethical concerns related to using art-based supervision strategies tend to coalesce around the topics of practicing outside of the scope of professional training, handling of artwork, and ensuring supervisee well-being.…”
Section: Ethical Considerationsmentioning
confidence: 99%
“…Supervisors should institute safeguards for supervisee well-being and be prepared for unintended consequences. Morrissette and Gadbois (2006) made several recommendations for protecting student well-being in the educational setting that have applicability to the supervision context. Supervisors should inform supervisees of the rationale for including art-based techniques, including the goal and purpose, and inform supervisees of the potential for unintentional self-disclosures and emotional responses.…”
Section: Ethical Considerationsmentioning
confidence: 99%
“…Thus, counselor-educators can choose from a wide variety of teaching strategies when designing an educational experience that will have the greatest impact on student learning. Often, counseloreducators choose to combine methods to allow students the opportunity to learn and interact with content on multiple levels (Morrissette & Gadbois, 2006). However, authors have identified potential obstacles counseloreducators may experience when deciding to implement a specific educational strategy involving role-play and technology.…”
mentioning
confidence: 99%
“…Some considerations should include the student learner's culture, comfort level, and learning style (Morrissette & Gadbois, 2006). Some participants struggled with visual thinking and expressing complex ideas, noting that they felt they could more adequately convey their thoughts through the CDCA written version.…”
Section: Difficulties Of Artmaking Artmaking Was Not Universally Sucmentioning
confidence: 99%
“…Morrissette and Gadbois (2006) cautioned counselor educators who employ teaching strategies that invite self-exploration and reflection, such as is inherent in experiential learning, of the possibility of evoking student anxiety and provoking unintentional consequences. Counselor educators who include such activities should be trained in both group process and experiential-based teaching (Westwood, 1994).…”
Section: Multicultural Counselor Educationmentioning
confidence: 99%